2018
DOI: 10.1002/jmri.26586
|View full text |Cite
|
Sign up to set email alerts
|

3T chemical shift‐encoded MRI: Detection of altered proximal femur marrow adipose tissue composition in glucocorticoid users and validation with magnetic resonance spectroscopy

Abstract: Background Osteoporosis (OP) results in weak bone and can ultimately lead to fracture. Drugs such as glucocorticoids can also induce OP (glucocorticoid‐induced osteoporosis [GIO]). Bone marrow adipose tissue composition and quantity may play a role in OP pathophysiology, but has not been thoroughly studied in GIO compared to primary OP. Purpose/Hypothesis Chemical shift‐encoded (CSE) MRI allows detection of subregional differences in bone marrow adipose tissue composition and quantity in the proximal femur of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…51 Most recently, Martel et al measured unsaturated and saturated lipid fractions in the proximal femur of osteoporosis patients with MRI and MRS, with a good correlation between the methods (r ~ 0.98) and a small bias (~2 percentage points). 67 Another recent study by Nemeth et al, in which visceral and subcutaneous fat of volunteers were investigated, also found fair agreement between MRS and MRI (ndb: r = 0.82, bias = 0.06, nmidb: r = 0.82, bias = 0.02). 51 However, both methods overestimated ndb and nmidb compared to GC (bias 0.24 and 0.19, respectively), similar to previous in vitro and in vivo validation studies.…”
Section: Validation and Performance Evaluationmentioning
confidence: 87%
See 4 more Smart Citations
“…51 Most recently, Martel et al measured unsaturated and saturated lipid fractions in the proximal femur of osteoporosis patients with MRI and MRS, with a good correlation between the methods (r ~ 0.98) and a small bias (~2 percentage points). 67 Another recent study by Nemeth et al, in which visceral and subcutaneous fat of volunteers were investigated, also found fair agreement between MRS and MRI (ndb: r = 0.82, bias = 0.06, nmidb: r = 0.82, bias = 0.02). 51 However, both methods overestimated ndb and nmidb compared to GC (bias 0.24 and 0.19, respectively), similar to previous in vitro and in vivo validation studies.…”
Section: Validation and Performance Evaluationmentioning
confidence: 87%
“…While absolute in vivo quantification of the fatty acid composition is challenging also with MRS, it is nevertheless commonly used as a reference for the MRI-based methods, because of the practical difficulties to use GC as a reference. Promising agreement with MRS results has been found in adipose tissue and bone marrow, 51,66,67 but one group did note a large intra-subject variability and commented on the need for masking of extreme values. 51 Most recently, Martel et al measured unsaturated and saturated lipid fractions in the proximal femur of osteoporosis patients with MRI and MRS, with a good correlation between the methods (r ~ 0.98) and a small bias (~2 percentage points).…”
Section: Validation and Performance Evaluationmentioning
confidence: 87%
See 3 more Smart Citations